2014
DOI: 10.1017/s1041610214000854
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of dementia care in rural China

Abstract: Many countries face policy challenges related to the well-being of their aging populations, and China, with the world's largest aging population, is no different. Over the past 40 years, China has experienced demographic transition toward an “aging society.” According to the National Bureau of Statistics in China (NBSC), the number of people aged 60 years and older in China has risen to 185 million, with rural areas aging more rapidly during China's demographic transition (National Bureau of Statistics of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…Dementia‐related stigma is pervasive across the globe and may be affecting ethnic or immigrant minorities to a greater extent . Chen et al reported that culturally there is stigma in China where people with dementia face ridicule, misunderstanding, isolation, discrimination, and even abuse . The theme of stigma (towards the person people living with dementia and family, and health care) found in our study is not unique.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Dementia‐related stigma is pervasive across the globe and may be affecting ethnic or immigrant minorities to a greater extent . Chen et al reported that culturally there is stigma in China where people with dementia face ridicule, misunderstanding, isolation, discrimination, and even abuse . The theme of stigma (towards the person people living with dementia and family, and health care) found in our study is not unique.…”
Section: Discussionmentioning
confidence: 46%
“…20 Chen et al reported that culturally there is stigma in China where people with dementia face ridicule, misunderstanding, isolation, discrimination, and even abuse. 21 The theme of stigma (towards the person people living with dementia and family, and health care) found in our study is not unique. For example, a recent review that included western and non-western studies classified stigma towards dementia as public stigma (members of the community), professional and structural stigma (institutions, public policy, health care professionals, etc.…”
Section: Discussionmentioning
confidence: 54%
“…As family structures are changing, particularly with migration from rural to urban areas in LMICs, the number of people living alone or with a partner rather than in extended family structure is increasing (Chen et al, 2014). Very little research emerged on women with dementia without family caregivers, or the impact of migration of younger family members on care provision for the older family members remaining behind.…”
Section: Discussionmentioning
confidence: 99%
“…25 Our participants also raised the issue of stigma in rural communities as a barrier to seeking support and as a contributor to social isolation. Another study described the significant problems faced by China in caring for rural older people with dementia, specifically the very large number of older people experiencing dementia, the erosion of the traditional model of families providing elder care, the lack of services in rural areas and the substantial stigma that is attached to dementia.…”
Section: Support For Communitiesmentioning
confidence: 97%